Análise da eficiência de extratos vegetais para aplicação como inibidores de corrosão - Quadros, Gabriel Porto (2019)
Naturals inhibitors can be obtained through vegetable extracts or biomass sources, contributing to attenuate the oxidative process, reducing the corrosion and being an alternative ecofriendly. Recent researches, show that many plants has in their composition, composts with antioxidant actions, mainly polyphenols. Thus, this study has the aim of analyze the efficiency of vegetables extracts obtained from domestic/agroindustry subproducts as corrosion inhibitors in acid mean. The metalic samples are made of carbon steel SAE 1020 and it stayed at imersion in solution by 21 days, being analyzed every week. The waste used were coffee and mate herb (Ilex paraguariensis). The corrosion mean was solution of HCl 1 mol. L-1 . Proof bodies were caracterized by cut technics, polishing, pachymetry and rugosity, making possible plane surface and uniform samples for the corrosion tests. Also, it was test the different solutions for the extraction of phenolics composts, it has show that etanol/water (60/40) presented the best conditions for the determination of this composts. The total phenols of the vegetable extracts were determinated by the Folin Ciocalteau method, with teor of 322.12 ± 0.59 mg EAG.g-1 for coffee waste and 375.25 ± 0.73 mg EAG.g-1 for mate herb waste. Besides, it was used UV/Vis spectroscopy and FTIR on vegetable extracts and the DRX technique at the corrosion products, for the identification of the organic composts. For surface analyze the optical microscopy were performed at the end of the 21 day. This technique confirmed that the organic composts from coffee and mate herb waste are directly associated to corrosion protection. Electrochemical technics as Cyclic Voltammetry and EIS were used to understand the interaction among this organic composts and the surface electrode. Loss mass measures also were performed and this way it was possible verify the corrision rate, for 0,5 g.L-1 mate herb waste of 4.98 ± 0.20 mm.ano-1 with efficiency of 52.78 ± 2.72 % and the 1.0 g.L-1 coffee waste showed a corrision rate of 4.99 ± 0.18 mm ano-1 and efficiency of 51.45 ± 2.59 %. This way, the 0.5 g.L-1 mate herb waste and 1.0 g.L-1 coffee waste presented the best results combating the corrosion.